2009
DOI: 10.1016/j.amepre.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Social Smoking

Abstract: Background-Social smoking is increasingly prevalent and poses a challenge to traditional cessation practices. Tobacco companies conducted extensive research on social smokers long before health authorities did and marketed products to promote this smoking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 22 publications
(30 reference statements)
5
50
0
Order By: Relevance
“…Consistent with previous research, the nondaily smokers had higher SES than daily smokers, 11,17,23,24 most self-identified as a nonsmoker, 1 they were more likely than daily smokers to be motivated by social reasons rather than craving or addiction, 11,25 and they had a higher prevalence of weekly binge drinking. 5,26 The low-rate daily smokers were of higher SES than high-rate daily smokers, which is also consistent with previous research.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with previous research, the nondaily smokers had higher SES than daily smokers, 11,17,23,24 most self-identified as a nonsmoker, 1 they were more likely than daily smokers to be motivated by social reasons rather than craving or addiction, 11,25 and they had a higher prevalence of weekly binge drinking. 5,26 The low-rate daily smokers were of higher SES than high-rate daily smokers, which is also consistent with previous research.…”
Section: Discussionsupporting
confidence: 75%
“…11 As early as the 1970s, confidential industry research found that social smokers represented 20% to 25% of all smokers and had varying socioeconomic backgrounds, levels of education, and ethnicities. 11 Industry research found that social smokers often did not identify themselves as smokers and denied nicotine dependence.…”
Section: Social Smokers: a Subset Of Nondaily Smokersmentioning
confidence: 99%
“…11 As early as the 1970s, confidential industry research found that social smokers represented 20% to 25% of all smokers and had varying socioeconomic backgrounds, levels of education, and ethnicities. 11 Industry research found that social smokers often did not identify themselves as smokers and denied nicotine dependence. 11 They purchased cigarettes primarily by the pack to limit consumption, smoking on average fewer than 10 cigarettes a day, while commonly smoking more on weekends or at parties.…”
Section: Social Smokers: a Subset Of Nondaily Smokersmentioning
confidence: 99%
“…The majority of adolescents in our study sample (73.3%) defined social smoking as smoking primarily in social contexts (i.e., at parties only). Evidence has shown that social smokers tend to categorize themselves as nonsmokers when asked by family, friends, or health care providers (Schane, Glantz, & Ling, 2009). As a result, general health messages that are used to target youth smokers may be ineffective if they contain terms such as "smoker" because these individuals do not view their smoking behavior as a marker of such behavior (Gilpin, White, & Pierce, 2005;Moran et al, 2004) and may not perceive the messages as applicable.…”
Section: Discussionmentioning
confidence: 97%